Effect of Resistance Exercises by Means of Aids with Doses of Vitamin D3 in Some Biomechanical Variants to Develop the Spike Skill of Volleyball for Female Students - Mohammed Jasim Mohammed Al-Khalidi (Journal of Global Pharma Technology, 2016)
The research focused on several axes focused on these axes to know the impact of resistance exercises using the aids with doses of vitamin D3 to develop the skill of beating overwhelming volleyball and try to reach the best achievement, as the use of different aids shapes and sizes, taking into account differences in lengths and abilities for sample members to help Students to master this skill as required. The experimental group was trained on the skill of beating overwhelming by using aids with a dose of (1g) daily of vitamin D3 within 6 weeks at the rate of two training units per week and after the end of this period the results were collected for the two groups and the comparison between them (experimental group, control group) The statistic exceeds the experimental group on the control group.Keywords: Resistance exercises, Vitamin D3, biomechanical variants and spike skill.